2018
DOI: 10.1113/jp275733
|View full text |Cite
|
Sign up to set email alerts
|

Sinusoidal voltage protocols for rapid characterisation of ion channel kinetics

Abstract: Key points Ion current kinetics are commonly represented by current–voltage relationships, time constant–voltage relationships and subsequently mathematical models fitted to these. These experiments take substantial time, which means they are rarely performed in the same cell.Rather than traditional square‐wave voltage clamps, we fitted a model to the current evoked by a novel sum‐of‐sinusoids voltage clamp that was only 8 s long.Short protocols that can be performed multiple times within a single cell will of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
180
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(188 citation statements)
references
References 49 publications
8
180
0
Order By: Relevance
“…The implementation of the Milnes protocol might be best suited for manual patch techniques later in the drug discovery process conducted for risk assessments requiring more extensive characterization on a few candidate compounds (or for regulatory submissions). Beattie et al 20 and Lei et al 21,22 recently published voltage protocols more amenable to APC approaches to characterizing the kinetics of hERG block that might prove as suitable alternatives to the Milnes voltage clamp protocol.…”
Section: A Comment On the Milnes Dynamic Block Voltage Clamp Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementation of the Milnes protocol might be best suited for manual patch techniques later in the drug discovery process conducted for risk assessments requiring more extensive characterization on a few candidate compounds (or for regulatory submissions). Beattie et al 20 and Lei et al 21,22 recently published voltage protocols more amenable to APC approaches to characterizing the kinetics of hERG block that might prove as suitable alternatives to the Milnes voltage clamp protocol.…”
Section: A Comment On the Milnes Dynamic Block Voltage Clamp Protocolmentioning
confidence: 99%
“…Differences in the ratio of overexpressed current of interest (e.g., hERG) vs. endogenous background currents may lead to underestimates of blocking potency if background currents are not considered. For example, some authors prefer CHO cells over HEK cells as a hERG expression system based on generally lower background endogenous currents 20 . These differences may be corrected based on background currents measured at the end of each experiment in the presence of complete hERG block (e.g., with a maximal blocking concentration of a specific hERG blocking agent such as E-4031).…”
Section: A Comment On the Milnes Dynamic Block Voltage Clamp Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale for this approach was an assumption that kinetic parameters are determined by biophysics, and so less prone to variation than the expression of ion channels, pumps, and exchangers. However, a detailed sensitivity analysis of I Kr dynamics in the Courtemanche model showed that these kinetic parameters influence APD (Chang et al, 2017), and other studies have highlighted difficulties in calibrating ion channel dynamics using traditional approaches as well as showing that different formulations can have an important effect on the magnitude and time course of an ion channel current (Beattie et al, 2018). In the present study our focus was on the action potential rather than Ca 2+ handling, and a detailed sensitivity analysis of the mechanisms of Ca 2+ storage, release, and uptake in each model would be a valuable extension to the work presented here.…”
Section: Choice Of Inputsmentioning
confidence: 99%
“…The rationale for this approach was an 501 assumption that kinetic parameters are determined by biophysics, and so less prone to 502 variation than the expression of ion channels, pumps, and exchangers. However, a 503 detailed sensitivity analysis of I Kr dynamics in the Courtemanche model showed that 504 these kinetic parameters influence APD [44], and other studies have highlighted 505 difficulties in calibrating ion channel dynamics using traditional approaches as well as 506 showing that different formulations can have an important effect on the magnitude and 507 time course of an ion channel current [45]. In the present study our focus was on the 508 action potential rather than Ca 2+ handling, and a detailed sensitivity analysis of the 509 mechanisms of Ca 2+ storage, release, and uptake in each model would be a valuable 510 extension to the work presented here.…”
mentioning
confidence: 99%